A comparative investigation of azole susceptibility in Candida isolates from vulvovaginal candidiasis and recurrent vulvovaginal candidiasis patients in Ghana. (11th November 2016) - Adjapong, Gloria; Hale, Marie; Garrill, Ashley
Abstract: Vulvovaginal candidiasis (VVC) and recurrent vulvovaginal candidiasis (RVVC) affect millions of women and are typically treated with azoles. We know little about azole susceptibility of Candida species from VVC versus RVVC patients, and nothing about African isolates. We have investigated the susceptibility of Candida isolates from Ghana to fluconazole, itraconazole and/or voriconazole. The percentage of Candida albicans isolates showing susceptibility was significantly lower in RVVC than VVC patients. Isolates of Candida parapsilosis and Candida tropicalis showed a similar trend. For Candida glabrata there was no observed difference. The data indicate a decreased susceptibility in selected Candida species from RVVC patients.